Water treatment agent for synergistically removing fluorine and heavy metals and preparation method thereof
A highly efficient water treatment agent was prepared by leveraging the synergistic effect of aluminum-based flocculants, modified montmorillonite, and thiolated chitosan. This agent solves the problem of simultaneously removing fluoride ions and heavy metal ions from wastewater in existing technologies, achieving efficient and stable wastewater treatment results.
Patent Information
- Application Number
- CN202610699948.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-20
- Publication Date
- 2026-06-26
AI Technical Summary
Existing technologies are insufficient for efficiently and simultaneously removing fluoride ions and various heavy metal ions from wastewater, and existing adsorbents suffer from problems such as separation difficulties, high preparation costs, and poor stability.
By utilizing the synergistic effect of aluminum-based flocculants, organic ligands, modified montmorillonite, polymetallic salts, and thiolated chitosan, water treatment agents were prepared through pulsed ultrasound and microwave radiation to achieve efficient and simultaneous removal of fluoride ions and heavy metal ions.
It achieves efficient, deep, and simultaneous removal of fluoride ions and various heavy metal ions from wastewater, with high removal efficiency, good water treatment agent stability, and reduced agent costs and the risk of secondary pollution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of wastewater treatment, and more specifically, to a water treatment agent for synergistic removal of fluoride and heavy metals and its preparation method. Background Technology
[0002] With the rapid development of modern industry, the composition of wastewater discharged from industries such as mining, electroplating, electronics, battery manufacturing, and chemicals is becoming increasingly complex. Among these, the combined pollution problem of fluoride ions and heavy metal ions (such as lead, cadmium, copper, and mercury) is particularly prominent. Excessive intake of fluoride ions can lead to dental fluorosis and skeletal fluorosis in humans, while heavy metal ions are highly toxic, bioaccumulative, and non-degradable. When the two coexist, they often produce synergistic toxic effects, seriously threatening ecological security and human health.
[0003] Currently, the main technologies for treating fluoride and heavy metal wastewater include chemical precipitation, ion exchange, membrane separation, and adsorption. Chemical precipitation (such as lime precipitation for fluoride removal and hydroxide precipitation for heavy metal removal) is widely used due to its simplicity and low cost. However, chemical precipitation requires large amounts of reagents, and the optimal precipitation pH varies significantly for different pollutants, making simultaneous and efficient removal difficult. Furthermore, the reaction process generates large amounts of highly water-content chemical sludge, which is typically classified as hazardous waste, resulting in high subsequent treatment and disposal costs and a risk of secondary pollution.
[0004] Ion exchange and membrane separation methods can achieve good effluent quality, but their application in large-scale wastewater treatment is limited by factors such as large equipment investment, high operating costs, easy membrane fouling and clogging, and difficulty in treating ion exchange resin regeneration waste liquid.
[0005] Adsorption is a promising deep treatment technology with advantages such as flexibility, ease of operation, and recyclability of adsorbents.
[0006] Patent CN106744736B discloses an active porous boron nitride nanosheet with a high adsorption capacity for heavy metals; CN107321327A discloses a polypyrrole / reduced graphene oxide aerogel that can synergistically adsorb chromium (VI) and bisphenol A. However, such high-performance adsorbent materials have the following problems: (1) Difficult to separate and recover, nano or powdered adsorbents are difficult to separate from water by simple precipitation or filtration after use, which can easily cause material loss and secondary pollution; (2) High preparation cost, involving complex processes such as high-temperature calcination and freeze drying, and expensive raw materials, making it difficult to achieve industrial production and large-scale application; (3) Single function or poor synergy, most existing adsorbents are mainly for single types of pollutants, and the simultaneous treatment efficiency of fluoride ion and heavy metal ion coexisting systems is not ideal.
[0007] To improve separation performance, magnetic materials can be added to the adsorption process, such as combining Fe3O4 nanoparticles with the active component to impart magnetic responsiveness to the adsorbent, thereby enabling rapid solid-liquid separation through an external magnetic field. However, existing magnetic composite adsorbents still have shortcomings: on the one hand, the active component, which is simply physically loaded, is prone to detachment during use, leading to adsorption performance degradation and poor cycle stability; on the other hand, most magnetic adsorbents have a limited range of functional groups, resulting in limited ability to integrate and capture different types of heavy metal ions and fluoride ions.
[0008] Therefore, there is an urgent need to develop a new type of water treatment adsorbent that can simultaneously and efficiently remove fluoride ions and various heavy metal ions from wastewater. Summary of the Invention
[0009] The purpose of this invention is to provide a water treatment agent that synergistically removes fluoride and heavy metals. Through the synergistic effect of aluminum-based flocculants, organic ligands, modified montmorillonite, polymetallic salts, and thiolated chitosan, it can efficiently, deeply, and simultaneously remove fluoride ions and various heavy metal ions from wastewater. The removal efficiency is high and the water treatment agent has good stability.
[0010] Another objective of this invention is to provide a method for preparing a water treatment agent that synergistically removes fluoride and heavy metals. The method involves using pulsed ultrasound to fully disperse montmorillonite and pre-intercalate metal ions, followed by microwave radiation to crosslink chitosan with multiple metal ions and to induce interlayer insertion of organic macromolecules. This shortens the reaction time, and the product exhibits numerous active sites, structural uniformity, and strong metal ion anchoring, resulting in a water treatment agent with excellent fluoride and heavy metal removal performance.
[0011] The technical problem solved by this invention is achieved by the following technical solution.
[0012] On one hand, embodiments of the present invention provide a water treatment agent for synergistic removal of fluoride and heavy metals, comprising the following raw materials by weight: 100 parts water, 10-30 parts aluminum-based flocculant, 0.5-3 parts citric acid, 2-10 parts modified montmorillonite, 1-3 parts cerium chloride heptahydrate, 1-8 parts calcium chloride, 1-3 parts soluble zirconium salt, 2-4 parts thiolated chitosan, and 2-3 parts stabilizer.
[0013] In some embodiments of the present invention, the raw materials include the following by weight: 100 parts water, 20 parts aluminum-based flocculant, 1.5 parts citric acid, 5 parts modified montmorillonite, 1.5 parts cerium chloride heptahydrate, 4 parts calcium chloride, 1.5 parts soluble zirconium salt, 2 parts thiolated chitosan, and 2.5 parts stabilizer.
[0014] In some embodiments of the present invention, the aluminum-based flocculant is polyaluminum chloride; the stabilizer is ethylene glycol or glycerol.
[0015] In some embodiments of the present invention, the modified montmorillonite is FeOOH intercalated modified montmorillonite, and the preparation method of the modified montmorillonite includes the following steps: (1) Disperse montmorillonite in dilute hydrochloric acid solution and stir and reflux at 60-80℃ for 2-6 hours; wash with water until pH>5, centrifuge, dry, grind through a 200-mesh sieve to obtain acid-activated montmorillonite; (2) Disperse acid-activated montmorillonite in FeCl3 solution, stir for 12-24 hours, centrifuge to separate, disperse the solid in water, adjust the pH to 6-8, age at 60-80℃ for 2-4 hours, and the product is centrifuged, washed and dried to obtain functionalized montmorillonite; (3) Disperse functionalized montmorillonite in a mixed solution of ethanol and water, add silane coupling agent, adjust pH to 4-5, stir and react at 50-70℃ for 4-8 hours, centrifuge, wash until neutral, and dry to obtain modified montmorillonite.
[0016] In some embodiments of the present invention, the concentration of the dilute hydrochloric acid solution is 0.5-2 mol / L, and the mass-to-volume ratio of montmorillonite to dilute hydrochloric acid solution is 1g:10mL-1g:20mL; The concentration of FeCl3 solution is 0.1-0.5 mol / L, and the mass-to-volume ratio of functionalized montmorillonite to FeCl3 solution is 1g:10mL-1g:30mL.
[0017] In some embodiments of the present invention, the concentration of the dilute hydrochloric acid solution is 1-1.5 mol / L, and the mass-to-volume ratio of montmorillonite to dilute hydrochloric acid solution is 1g:15mL. The concentration of FeCl3 solution is 0.2-0.3 mol / L, and the mass-to-volume ratio of functionalized montmorillonite to FeCl3 solution is 1g:20mL.
[0018] In some embodiments of the present invention, the method for preparing the thiolated chitosan includes the following steps: Chitosan was dissolved in an aqueous acetic acid solution, and thiol reagent, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide were added. The mixture was stirred at room temperature for 4-8 hours. After the reaction was completed, the pH was adjusted to 8-9, centrifuged, washed with water until neutral, and dried to obtain thiolized chitosan.
[0019] In some embodiments of the present invention, the molar ratio of chitosan to thiol reagent is 1:0.5-1:2; the thiol reagent is at least one of thioglycolic acid and L-cysteine.
[0020] On the other hand, embodiments of the present invention provide a method for preparing a water treatment agent that synergistically removes fluoride and heavy metals, comprising the following steps: S1, add aluminum-based flocculant and citric acid to water, stir until dissolved to obtain matrix solution; S2, add modified montmorillonite to the matrix solution, disperse by pulsed ultrasonication for 5-10 min, then add cerium chloride, calcium chloride and soluble zirconium salt, stir evenly, and then add acid regulator to adjust the pH of the system to 2.5-4.0. S3, then add an acidic solution of thiolated chitosan, and in a microwave reactor, stir at 40-50°C for 10-15 minutes. After cooling, add a stabilizer and stir until homogeneous to obtain the water treatment agent.
[0021] In some embodiments of the present invention, the frequency of the pulsed ultrasound is 20-30kHz, the power density is 150-200W / L, the operation time is 3-5s, and the pause time is 1-2s; the power of the microwave reactor is 400-500W, the operation time is 40s, and the pause time is 20s.
[0022] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects: The water treatment agent provided by this invention achieves efficient, deep, and simultaneous removal of fluoride ions and various heavy metal ions from wastewater through the synergistic effect of aluminum-based flocculants, organic ligands, modified montmorillonite, polymetallic salts, and thiolated chitosan. It has high removal efficiency and good stability.
[0023] The four metal ions of calcium, cerium, aluminum, and zirconium work synergistically to achieve rapid precipitation, deep complexation, and flocculation adsorption, thus removing fluoride from wastewater. The thiol, amino, hydroxyl groups, and negatively charged sites between the montmorillonite layers can jointly chelate and adsorb multiple heavy metal ions, thereby achieving the simultaneous removal of fluoride and multiple heavy metal ions.
[0024] Thiol-modified chitosan and modified montmorillonite interact through coordination bonds and intercalation to form Al 3+ Zr 4+ Ce 3+ When metal ions are anchored to a solid carrier, the leaching rate of metal ions is low during water treatment, and there is no risk of secondary pollution.
[0025] The water treatment agent preparation method provided by this invention involves using pulsed ultrasound to fully disperse montmorillonite and pre-intercalate metal ions, followed by microwave radiation to crosslink chitosan with multiple metal ions and induce interlayer insertion of organic macromolecules. This shortens the reaction time, and the product exhibits numerous active sites, structural uniformity, and strong metal ion anchoring, resulting in a water treatment agent with excellent defluorination and heavy metal removal properties. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0027] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other. The present invention will now be described in detail with reference to specific embodiments.
[0028] A water treatment agent for synergistic removal of fluoride and heavy metals, comprising the following raw materials by weight: 100 parts water, 10-30 parts aluminum-based flocculant, 0.5-3 parts citric acid, 2-10 parts modified montmorillonite, 1-3 parts cerium chloride heptahydrate, 1-8 parts calcium chloride, 1-3 parts soluble zirconium salt, 2-4 parts thiolated chitosan, and 2-3 parts stabilizer.
[0029] In some embodiments of the present invention, the raw materials include the following by weight: 100 parts water, 20 parts aluminum-based flocculant, 1.5 parts citric acid, 5 parts modified montmorillonite, 1.5 parts cerium chloride heptahydrate, 4 parts calcium chloride, 1.5 parts soluble zirconium salt, 2 parts thiolated chitosan, and 2.5 parts stabilizer.
[0030] In some embodiments of the present invention, the aluminum-based flocculant is polyaluminum chloride; the stabilizer is ethylene glycol or glycerol.
[0031] The water treatment agent provided in this embodiment of the invention has the following effects on each component: Aluminum-based flocculant, polyaluminum chloride (PAC), is a major flocculant and defluorinating agent. Its mechanism of action is as follows: Al... 3+ In aqueous solution, it gradually hydrolyzes to form polynuclear hydroxy complexes (such as Al). 13 O4(OH) 24 7+ Highly charged cations compress the electrical double layer of colloidal particles through charge neutralization, destabilizing them; aluminum hydroxyl ions can undergo ligand exchange with fluoride ions to form hydroxyaluminum fluoride complex precipitates, thereby removing fluoride from water. The flocs formed by aluminum-based flocculants have a net-catching and sweeping function, which can accelerate solid-liquid separation.
[0032] Citric acid is used as a pre-complexing agent and stabilizer. The carboxyl group in its molecule can react with Al... 3+ Zr 4+ Ce 3+Citric acid forms soluble five- or six-membered ring complexes with high-valence metal ions, thereby delaying the hydrolysis and precipitation of these metal ions under acidic conditions (pH 2.5-4.0) and improving the storage stability of liquid reagents. In wastewater treatment, citric acid can also help maintain a suitable pH environment by competing for protons, preventing premature deactivation of metal ions.
[0033] Cerium chloride heptahydrate provides Ce for water treatment agents 3+ It reacts with fluoride ions to form poorly soluble cerium fluoride, exhibiting excellent removal efficiency for low concentrations of fluoride (≤5 mg / L), stably reducing fluoride ions in effluent to below 0.5 mg / L, meeting the Class III surface water standard. Furthermore, Ce... 3+ It can also coordinate with the amino and hydroxyl groups of chitosan to participate in the construction of a three-dimensional cross-linked network, thereby enhancing the overall stability of the drug.
[0034] Calcium chloride provides calcium ions to water treatment agents, enabling the rapid precipitation of high concentrations of fluoride. 2+ It reacts with F- to form calcium fluoride precipitate. This reaction is fast and can quickly reduce the fluoride load in wastewater during treatment, especially suitable for situations where the initial fluoride concentration is >20 mg / L.
[0035] Soluble zirconium salts, such as ZrOCl2·8H2O, are synergistic components for fluorine and arsenic removal. The provided Zr... 4+ In aqueous solution, it forms strongly positively charged hydroxyzirconium ions, which have a strong affinity for fluoride and arsenate ions, forming stable Zr-F or Zr-As complexes that precipitate. Meanwhile, Zr... 4+ As a high-valence metal ion, it can coordinate with multiple sites (-NH2, -OH, -SH) on the chitosan molecular chain, enhance the cross-linking network density, and reduce the leaching risk of metal ions.
[0036] Stabilizers improve the storage stability and antifreeze properties of liquid pharmaceuticals. The hydroxyl groups in polyol molecules form a strong hydrogen bond network with water molecules, which lowers the freezing point of the pharmaceuticals, preventing freezing during winter transportation or storage; it also inhibits the crystallization or gelation of chitosan molecular chains at low temperatures, extending shelf life. Simultaneously, stabilizers increase the viscosity of water treatment agents and slow down the settling rate of montmorillonite particles, ensuring product uniformity and stability throughout its shelf life.
[0037] In some embodiments of the present invention, the modified montmorillonite is FeOOH intercalated modified montmorillonite, and the preparation method of the modified montmorillonite includes the following steps: (1) Disperse montmorillonite in dilute hydrochloric acid solution and stir and reflux at 60-80℃ for 2-6 hours; wash with water until pH>5, centrifuge, dry, grind through a 200-mesh sieve to obtain acid-activated montmorillonite; (2) Disperse acid-activated montmorillonite in FeCl3 solution, stir for 12-24 hours, centrifuge to separate, disperse the solid in water, adjust the pH to 6-8, age at 60-80℃ for 2-4 hours, and the product is centrifuged, washed and dried to obtain functionalized montmorillonite; (3) Disperse functionalized montmorillonite in a mixed solution of ethanol and water, add silane coupling agent, adjust pH to 4-5, stir and react at 50-70℃ for 4-8 hours, centrifuge, wash until neutral, and dry to obtain modified montmorillonite.
[0038] First, acid activation treatment significantly increases the specific surface area of montmorillonite and greatly enhances the number of silanol and aluminol hydroxyl groups on its surface, providing abundant sites for subsequent functionalization. Second, FeOOH nanopillar layers are introduced into the interlayer of montmorillonite, expanding the interlayer spacing to Al. 3+ Zr 4+ Ce 3+ And thiolated chitosan provides intercalation space, and FeOOH itself provides intercalation space for arsenic (As(III), As(V)) and lead (Pb). 2+ Heavy metals such as fluoride ions and chitosan exhibit specific adsorption capabilities. Finally, by grafting with a silane coupling agent, functional groups such as amino (-NH2) and thiol (-SH) are introduced into the surface and interlayer of montmorillonite, enhancing its chemical connection with metal ions and chitosan. The modified montmorillonite possesses both high specific surface area, high cation exchange capacity, and multiple adsorption sites, effectively capturing fluoride ions and heavy metal ions.
[0039] In some embodiments of the present invention, the concentration of the dilute hydrochloric acid solution is 0.5-2 mol / L, and the mass-to-volume ratio of montmorillonite to dilute hydrochloric acid solution is 1g:10mL-1g:20mL; The concentration of FeCl3 solution is 0.1-0.5 mol / L, and the mass-to-volume ratio of functionalized montmorillonite to FeCl3 solution is 1g:10mL-1g:30mL.
[0040] In some embodiments of the present invention, the concentration of the dilute hydrochloric acid solution is 1-1.5 mol / L, and the mass-to-volume ratio of montmorillonite to dilute hydrochloric acid solution is 1g:15mL. The concentration of FeCl3 solution is 0.2-0.3 mol / L, and the mass-to-volume ratio of functionalized montmorillonite to FeCl3 solution is 1g:20mL.
[0041] In some embodiments of the present invention, the method for preparing the thiolated chitosan includes the following steps: Chitosan was dissolved in an aqueous acetic acid solution, and thiol reagent, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide were added. The mixture was stirred at room temperature for 4-8 hours. After the reaction was completed, the pH was adjusted to 8-9, centrifuged, washed with water until neutral, and dried to obtain thiolized chitosan.
[0042] Thiol-modified chitosan serves as a heavy metal chelating agent and cross-linking backbone. On one hand, the provided thiol groups (-SH) are effective against mercury (Hg). 2 + ), lead (Pb) 2+ ), cadmium (Cd 2+ Heavy metal ions, such as α- and β-, have extremely high complexation constants and can form stable thiolate precipitates, achieving a removal rate of over 98%. On the other hand, the amino groups (-NH2) on the chitosan backbone become protonated and positively charged under acidic conditions, allowing them to remove some anionic pollutants (such as F-) through electrostatic adsorption. They can also react with Al... 3+ Zr 4+ Ce 3+ Metal ions form coordination bonds, fixing them within the gel network and reducing their leaching rate during water treatment. Hydroxyl groups (-OH) can form hydrogen bonds with the silanol groups on the surface of montmorillonite, strengthening the bond between the organic and inorganic interfaces. Thioyl chitosan forms a three-dimensional cross-linked network through metal ion bridging, embedding modified montmorillonite, metal active centers, etc., within the three-dimensional cross-linked network to form a self-stabilizing composite structure. The long polymer chains of chitosan can aggregate tiny flocs into large sediments through adsorption bridging, accelerating solid-liquid separation.
[0043] In some embodiments of the present invention, the molar ratio of chitosan to thiol reagent is 1:0.5-1:2; the thiol reagent is at least one of thioglycolic acid and L-cysteine.
[0044] On the other hand, embodiments of the present invention provide a method for preparing a water treatment agent that synergistically removes fluoride and heavy metals, comprising the following steps: S1, add aluminum-based flocculant and citric acid to water, stir until dissolved to obtain matrix solution; S2, add modified montmorillonite to the matrix solution, disperse by pulsed ultrasonication for 5-10 min, then add cerium chloride, calcium chloride and soluble zirconium salt, stir evenly, and then add acid regulator to adjust the pH of the system to 2.5-4.0. S3, then add an acidic solution of thiolated chitosan, and in a microwave reactor, stir at 40-50°C for 10-15 minutes. After cooling, add a stabilizer and stir until homogeneous to obtain the water treatment agent.
[0045] In some embodiments of the present invention, the frequency of the pulsed ultrasound is 20-30kHz, the power density is 150-200W / L, the operation time is 3-5s, and the pause time is 1-2s; the power of the microwave reactor is 400-500W, the operation time is 40s, and the pause time is 20s.
[0046] In step S1, aluminum ions undergo pre-complexation with citric acid to form a soluble aluminum-organic ligand complex, which effectively delays the rapid hydrolysis of aluminum ions in the subsequent acidic environment and prevents the aluminum salt from prematurely forming amorphous aluminum hydroxide precipitate and becoming deactivated. Citric acid, as a ligand, also provides a stable coordination environment for the subsequently introduced high-valence metal ions such as zirconium and cerium, allowing multiple metal ions to be uniformly dispersed in the solution without interference, thus laying the foundation for subsequent intercalation reactions with modified montmorillonite and cross-linking reactions with thiolated chitosan.
[0047] In step S2, pulsed ultrasonic treatment utilizes the cavitation effect of ultrasound to generate strong microjets and shock waves, breaking the micron-sized aggregates of modified montmorillonite into submicron or even nano-sized flakes, increasing the specific surface area and the exposure rate of interlayer edges; the local high temperature (about 5000 K) and high pressure (about 1000 atm) generated during cavitation provide the impetus for the rapid diffusion of metal ions such as aluminum, zirconium, and cerium into the montmorillonite interlayer, thereby improving the ion intercalation efficiency.
[0048] After ultrasonic dispersion, cerium chloride heptahydrate, calcium chloride, and soluble zirconium salt were added to the system to control the pH between 2.5 and 4.0. Under these acidic conditions, Al... 3+ Zr 4+ Ce 3+ All exist stably in the form of free ions or oligomeric hydroxyl ions; at the same time, the negative charge sites between the modified montmorillonite layers are fully exposed, and metal ions are introduced into the interlayer through electrostatic attraction and ion exchange; the acidic environment allows the chitosan added later to be fully dissolved, and the thiol groups remain in a reduced state.
[0049] In step S3, under a microwave field, the -NH2, -SH, and -OH groups on the thiolated chitosan molecular chains react with Al... 3+ Zr 4+ Ce 3 + Rapid coordination and cross-linking of metal ions leads to the formation of a dense three-dimensional network structure. Simultaneously, chitosan molecular chains, aided by microwaves, more readily insert into the interlayer of montmorillonite, forming an organic-inorganic composite pillared structure together with the pillared metal ions. After microwave cross-linking, modified montmorillonite, multivalent metal ions, and thiolized chitosan are bonded through coordination bonds, electrostatic interactions, and hydrogen bonds to form a gel system.
[0050] The features and performance of the present invention will be further described in detail below with reference to embodiments. Example 1 1. Preparation of modified montmorillonite: Montmorillonite powder was dispersed in a dilute hydrochloric acid solution (concentration 1.5 mol / L) at a solid-liquid ratio of 1:15, and stirred under reflux at 60-80℃ for 6 hours. After the reaction was completed, the mixture was washed with deionized water until pH > 5, centrifuged, dried at 80-105℃, and ground through a 200-mesh sieve to obtain acid-activated montmorillonite (H-MMT).
[0051] Acid-activated montmorillonite was dispersed in FeCl3 solution (0.3 mol / L) at a solid-liquid ratio of 1 g:20 mL, and stirred for ion exchange for 24 hours. After centrifugation, the solid was redispersed in deionized water at a solid-liquid ratio of approximately 1:10. Dilute NaOH solution (0.3 mol / L) was slowly added dropwise until the pH reached 6-8, with the addition rate controlled at 0.5-1 mL / min. The mixture was then aged in a 70°C water bath for 2 hours to allow the FeCl3 to mature. 3+ FeOOH nanopillars were generated through interlayer hydrolysis; the product was then separated by centrifugation and washed with deionized water until Cl-free. - Dry (70℃) to obtain FeOOH pillared montmorillonite (FeOOH-MMT).
[0052] FeOOH-pillared montmorillonite (FeOOH-MMT) was dispersed in an ethanol / water mixture (volume ratio 1:1), with a solid-liquid ratio of 1 g:15 ml. A measured amount of silane coupling agent (KH550, mass ratio to montmorillonite 1:10) was added, and the pH was adjusted to 4-5 with dilute acetic acid. The reaction was stirred at 60°C for 5 hours. After the reaction, the mixture was centrifuged, washed 2-3 times with ethanol, washed with deionized water until neutral, and then vacuum dried at 60°C to obtain modified montmorillonite.
[0053] 2. Preparation of thiolized chitosan: Chitosan was dissolved in an aqueous acetic acid solution (1.5% concentration, w / v). Thioglycolic acid was added, with a chitosan to thiol reagent molar ratio of 1:1. EDC·HCl (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and NHS (N-hydroxysuccinimide) were added as activators (both 8% of the chitosan mass), and the pH of the system was adjusted to 5. The mixture was stirred at room temperature for 8 hours under an inert atmosphere. After the reaction was complete, the pH was adjusted to 8-9 with NaOH to precipitate the product. The precipitate was separated by centrifugation, washed with deionized water until neutral, and then lyophilized or vacuum dried.
[0054] 3. Prepare the water treatment agent according to the following formula and method: 100 parts water, 20 parts aluminum-based flocculant (polyaluminum chloride, Aladdin), 1.5 parts citric acid, 5 parts modified montmorillonite, 1.5 parts cerium chloride heptahydrate, 4 parts calcium chloride, 1.5 parts soluble zirconium salt (zirconium oxychloride), 2 parts thiolated chitosan, and 2.5 parts stabilizer (ethylene glycol).
[0055] S1, add aluminum-based flocculant and citric acid to water, stir until dissolved to obtain matrix solution; S2, add modified montmorillonite to the matrix solution, disperse by pulsed ultrasonication for 5-10 min, then add cerium chloride, calcium chloride and soluble zirconium salt, stir evenly, and then add acid regulator to adjust the pH of the system to 2.5-4.0. S3, then add an acidic solution of thiolated chitosan, and in a microwave reactor, stir at 40-50°C for 10-15 minutes. After cooling, add a stabilizer and stir until homogeneous to obtain the water treatment agent.
[0056] The frequency of pulsed ultrasound is 20-30kHz, the power density is 150-200W / L, and it operates for 3-5 seconds with a 1-2 second pause. The power of the microwave reactor is 400-500W, and it operates for 40 seconds with a 20 second pause.
[0057] Example 2 The difference from Example 1 is that the formulation of the water treatment agent is as follows: 100 parts water, 10 parts aluminum-based flocculant, 0.5 parts citric acid, 2 parts modified montmorillonite, 1 part cerium chloride heptahydrate, 1 part calcium chloride, 1 part soluble zirconium salt, 2 parts thiolated chitosan, and 2 parts stabilizer.
[0058] The rest are the same as in Example 1.
[0059] Example 3 The difference from Example 1 is that the formulation of the water treatment agent is as follows: 100 parts water, 30 parts aluminum-based flocculant, 3 parts citric acid, 10 parts modified montmorillonite, 3 parts cerium chloride heptahydrate, 8 parts calcium chloride, 3 parts soluble zirconium salt, 4 parts thiolated chitosan, and 3 parts stabilizer.
[0060] The rest are the same as in Example 1.
[0061] Example 4 The difference from Example 1 is that the formulation of the water treatment agent is as follows: 100 parts water, 30 parts aluminum-based flocculant, 0.5 parts citric acid, 2 parts modified montmorillonite, 3 parts cerium chloride heptahydrate, 1 part calcium chloride, 3 parts soluble zirconium salt, 2 parts thiolated chitosan, and 3 parts stabilizer.
[0062] The rest are the same as in Example 1.
[0063] Example 5 The difference from Example 1 is that the formulation of the water treatment agent is as follows: 100 parts water, 10 parts aluminum-based flocculant, 3 parts citric acid, 10 parts modified montmorillonite, 1 part cerium chloride heptahydrate, 8 parts calcium chloride, 1 part soluble zirconium salt, 4 parts thiolated chitosan, and 2 parts stabilizer.
[0064] The rest are the same as in Example 1.
[0065] Experimental Example With fluorine (20.1 mg / L) and heavy metals (Pb) 2+ Cd 2+ Cr 3+ Taking the mixed simulated wastewater as an example, under the conditions of pH=6.5±0.2, stirring speed of 150r / min (fast stirring for 2min) + 50r / min (slow stirring for 10min), and sedimentation for 30min, the experimental data are shown in the table below: Table 1
[0066] To achieve the same removal effect (F) - When the concentration of fluoride is <1.0 mg / L and the concentration of heavy metals is <0.05 mg / L, the dosage of the defluorinating agent of this invention is only 60% of that of the prior art and 80% of that of commercially available PAC, which significantly reduces the cost of the agent.
[0067] (2) Storage stability test data Under normal temperature (25±2℃) and light-protected sealed conditions, a 180-day storage experiment was conducted on the defluorinating agent of this invention and commercially available PAC. The results are shown in the table below: Table 2
[0068] The defluorinating agent of this invention remains uniform and transparent after 180 days of storage, with a flocculation activity retention rate of >95%; while existing technologies show precipitation within 30 days and an activity decrease of >40%, proving that its storage stability is significantly better than that of existing technologies.
[0069] (3) Actual industrial wastewater verification data Selected wastewater containing fluorine and heavy metals from a photovoltaic enterprise (F - =80mg / L, Pb 2+ =15mg / L, total phosphorus =2.0mg / L) and fluoride-containing wastewater from an electroplating plant (F - =55mg / L, Cu 2+ A typical water sample (22 mg / L) was used for a pilot-scale test of a complete pretreatment-dosing-sedimentation-dehydration process. The data are as follows: Table 3 Photovoltaic wastewater containing fluorine and heavy metals
[0070] Table 4 Fluoride-containing wastewater from electroplating plants
[0071] Conclusion: In actual industrial wastewater, the defluorinating agent of this invention can stably reduce fluoride to below 0.8 mg / L, heavy metals to <0.05 mg / L, and sludge moisture content to <75%. Moreover, the sludge leaching toxicity is far below the limit of GB 5085.3-2007, and there is no risk of secondary pollution.
[0072] (4) Microscopic mechanism characterization data The changes in the potential of the colloidal particles before and after addition were compared using Zeta potential testing to verify charge neutralization and adhesion, as shown in the table below: Table 5
[0073] The defluorinating agent of this invention can change the zeta potential of colloidal particles from negative to positive, forming larger and denser flocs, increasing floc strength by about 70%, significantly improving charge neutralization capacity and floc adhesion, and providing favorable conditions for subsequent sludge dewatering.
[0074] The embodiments described above are some, but not all, embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A water treatment agent for synergistic removal of fluoride and heavy metals, characterized in that, By weight, it includes the following ingredients: 100 parts water, 10-30 parts aluminum-based flocculant, 0.5-3 parts citric acid, 2-10 parts modified montmorillonite, 1-3 parts cerium chloride heptahydrate, 1-8 parts calcium chloride, 1-3 parts soluble zirconium salt, 2-4 parts thiolated chitosan, and 2-3 parts stabilizer.
2. The water treatment agent for synergistic removal of fluoride and heavy metals according to claim 1, characterized in that, By weight, it includes the following ingredients: 100 parts water, 20 parts aluminum-based flocculant, 1.5 parts citric acid, 5 parts modified montmorillonite, 1.5 parts cerium chloride heptahydrate, 4 parts calcium chloride, 1.5 parts soluble zirconium salt, 2 parts thiolated chitosan, and 2.5 parts stabilizer.
3. The water treatment agent for synergistic removal of fluoride and heavy metals according to claim 1, characterized in that, The aluminum-based flocculant is polyaluminum chloride; the stabilizer is ethylene glycol or glycerol.
4. The water treatment agent for synergistic removal of fluoride and heavy metals according to claim 1, characterized in that, The modified montmorillonite is FeOOH intercalated modified montmorillonite, and the preparation method of the modified montmorillonite includes the following steps: (1) Disperse montmorillonite in dilute hydrochloric acid solution and stir and reflux at 60-80℃ for 2-6 hours; wash with water until pH>5, centrifuge, dry, grind through a 200-mesh sieve to obtain acid-activated montmorillonite; (2) Disperse acid-activated montmorillonite in FeCl3 solution, stir for 12-24 hours, centrifuge to separate, disperse the solid in water, adjust the pH to 6-8, age at 60-80℃ for 2-4 hours, and the product is centrifuged, washed and dried to obtain functionalized montmorillonite; (3) Disperse functionalized montmorillonite in a mixed solution of ethanol and water, add silane coupling agent, adjust pH to 4-5, stir and react at 50-70℃ for 4-8 hours, centrifuge, wash until neutral, and dry to obtain modified montmorillonite.
5. The water treatment agent for synergistic removal of fluoride and heavy metals according to claim 4, characterized in that, The concentration of the dilute hydrochloric acid solution is 0.5-2 mol / L, and the mass-to-volume ratio of montmorillonite to dilute hydrochloric acid solution is 1g:10mL-1g:20mL. The concentration of FeCl3 solution is 0.1-0.5 mol / L, and the mass-to-volume ratio of acid-activated montmorillonite to FeCl3 solution is 1g:10mL-1g:30mL.
6. The water treatment agent for synergistic removal of fluoride and heavy metals according to claim 5, characterized in that, The concentration of the dilute hydrochloric acid solution is 1-1.5 mol / L, and the mass-to-volume ratio of montmorillonite to the dilute hydrochloric acid solution is 1g:15mL. The concentration of FeCl3 solution is 0.2-0.3 mol / L, and the mass-to-volume ratio of acid-activated montmorillonite to FeCl3 solution is 1 g: 20 mL.
7. The water treatment agent for synergistic removal of fluoride and heavy metals according to claim 1, characterized in that, The method for preparing the thiolated chitosan includes the following steps: Chitosan was dissolved in an aqueous acetic acid solution, and thiol reagent, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide were added. The mixture was stirred at room temperature for 4-8 hours. After the reaction was completed, the pH was adjusted to 8-9, centrifuged, washed with water until neutral, and dried to obtain thiolized chitosan.
8. The water treatment agent for synergistic removal of fluoride and heavy metals according to claim 7, characterized in that, The molar ratio of chitosan to thiol reagent is 1:0.5-1:2; the thiol reagent is at least one of thioglycolic acid and L-cysteine.
9. A method for preparing a water treatment agent for synergistic removal of fluoride and heavy metals as described in any one of claims 1-8, characterized in that, Includes the following steps: S1, add aluminum-based flocculant and citric acid to water, stir until dissolved to obtain matrix solution; S2, add modified montmorillonite to the matrix solution, disperse by pulsed ultrasonication for 5-10 min, then add cerium chloride, calcium chloride and soluble zirconium salt, stir evenly, and then add acid regulator to adjust the pH of the system to 2.5-4.
0. S3, then add an acidic solution of thiolated chitosan, and in a microwave reactor, stir at 40-50°C for 10-15 minutes. After cooling, add a stabilizer and stir until homogeneous to obtain the water treatment agent.
10. The method for preparing the water treatment agent for synergistic removal of fluoride and heavy metals according to claim 9, characterized in that, The frequency of pulsed ultrasound is 20-30kHz, the power density is 150-200W / L, and it operates for 3-5 seconds with a 1-2 second pause. The microwave reactor has a power of 400-500W, operates for 40 seconds, and stops for 20 seconds.
Citation Information
Patent Citations
A kind of synthesis method of active porous boron nitride nanosheets for water treatment
CN106744736B
Preparation and application of graphene-based adsorbent synergistically adsorbing heavy metals and organic matters in water
CN107321327A